2013
DOI: 10.1016/j.biomaterials.2013.02.036
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of endothelial cell morphology, function, and survival using anisotropic nanofibrillar collagen scaffolds

Abstract: Endothelial cells (ECs) are aligned longitudinally under laminar flow, whereas they are polygonal and poorly aligned in regions of disturbed flow. The unaligned ECs in disturbed flow fields manifest altered function and reduced survival that promote lesion formation. We demonstrate that the alignment of the ECs may directly influence their biology, independent of fluid flow. We developed aligned nanofibrillar collagen scaffolds that mimic the structure of collagen bundles in blood vessels, and examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 52 publications
4
96
0
1
Order By: Relevance
“…24,43 The mechanism by which scaffold anisotropy modulates differentiation and cellular reorganization is not well-understood, but likely mediated by cell-ECM interactions. We previously showed that aligned nanofibrous scaffolds significantly upregulated the gene expression of integrin α1 subunit in primary human ECs, when compared to randomly oriented scaffolds Further work in this area will elucidate the signaling pathways by which anisotropic scaffolds modulate differentiation and cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…24,43 The mechanism by which scaffold anisotropy modulates differentiation and cellular reorganization is not well-understood, but likely mediated by cell-ECM interactions. We previously showed that aligned nanofibrous scaffolds significantly upregulated the gene expression of integrin α1 subunit in primary human ECs, when compared to randomly oriented scaffolds Further work in this area will elucidate the signaling pathways by which anisotropic scaffolds modulate differentiation and cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…[65,70,71] In addition to electrospinning, microscale fibrous substrates with various levels of filament density and alignment have been successfully developed by utilizing shear flow deposition within a microfluidic channel, making it compatible with other microfluidic cell culture components and systems. [72,73] …”
Section: Toolbox Of Micro/nanoengineered Functional Biomaterialsmentioning
confidence: 99%
“…1 In particular, the role of nanotopographical ECM organization on vascular endothelial cell (EC) structure and function is not well-understood, despite the presence of nano- to micro-scale fibrillar ECM networks within blood vessels. 2, 3 Although parallel-aligned (anisotropic) ECMs have been shown to direct cytoskeletal reorganization along the axis of patterning for numerous cell types, 4, 5 the physiological modulator of EC orientation is traditionally thought to be hemodynamic shear stress. 6, 7 In straight segments of vessels, the ECs that line the innermost layer morphologically are parallel-aligned along the direction of laminar blood flow.…”
mentioning
confidence: 99%